1987
DOI: 10.1029/gl014i004p00455
|View full text |Cite
|
Sign up to set email alerts
|

The May 2‐3, 1986 magnetic storm: First energetic ion composition observations with the Mics instrument on Viking

Abstract: Measurements with the Magnetospheric Ion Composition Spectrometer (MICS) onboard the polar orbiting Swedish satellite VIKING clearly show a strong asymmetry between the dusk‐ and dawnside ion distributions obtained after the onset of a magnetic storm on May 2‐3, 1986. The eveningside of the inner ring current region is quickly filled by protons with energies of some tens of keV. The morningside continues for several hours to show the quiet‐time inner ring current proton spectra in which protons below ∼100 keV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…[13] During storm intervals, a dawn-dusk asymmetry is often observed in the ion temperature images with the dawn side of the magnetosphere being cooler than the dusk side. Similar asymmetries in the ring current ion temperatures during storm times have been reported from in-situ measurements [Studemann et al, 1987]. Hints of a storm time dawn-dusk asymmetry in energetic neutral atom fluxes were also suggested in a modeling study of neutral atom emission observed by ISEE 1 [Roelof, 1987].…”
Section: Discussionsupporting
confidence: 62%
“…[13] During storm intervals, a dawn-dusk asymmetry is often observed in the ion temperature images with the dawn side of the magnetosphere being cooler than the dusk side. Similar asymmetries in the ring current ion temperatures during storm times have been reported from in-situ measurements [Studemann et al, 1987]. Hints of a storm time dawn-dusk asymmetry in energetic neutral atom fluxes were also suggested in a modeling study of neutral atom emission observed by ISEE 1 [Roelof, 1987].…”
Section: Discussionsupporting
confidence: 62%
“…Finally, the composition and energy per charge of ions from to to 326 keV Ie were recorded, using the magnetospheric ion com position spectrometer (MICS) [Stiidemann et al , 1987]. Pitch angle distributions were obtained for orbits 1103 and 893 by averaging over lO-min time periods to obtain adequate statistics.…”
Section: Eqmentioning
confidence: 99%
“…So far, in situ satellite observations have shown that a majority of the storm‐time enhancement of the tens‐of‐keV ion flux is in the premidnight sector. Stüdemann et al [1987] have shown that during the 2–3 May 1986 storm ( Dst minimum of −79 nT), the proton flux with 10–206 keV/q measured by the Viking satellite dramatically increased on the duskside (∼1800 MLT), while the proton spectrum was very similar to the quiet‐time one on the dawnside (∼0600 MLT). Similarly, during the main phase of the 10–11 April 1997 storm ( Dst minimum of −82 nT), a significant increase in the ion flux in the 30–80 keV energy range was also observed on the duskside (∼2000 MLT) by NOAA 12, while the flux remains almost steady on the dawnside (∼0800 MLT) [ Ebihara and Ejiri , 2000].…”
Section: Introductionmentioning
confidence: 99%